2020
DOI: 10.3389/fpls.2019.01657
|View full text |Cite
|
Sign up to set email alerts
|

A LysR-Type Transcriptional Regulator LcrX Is Involved in Virulence, Biofilm Formation, Swimming Motility, Siderophore Secretion, and Growth in Sugar Sources in Xanthomonas axonopodis Pv. glycines

Abstract: Xanthomonas axonopodis pv. glycines (Xag) is a Gram-negative bacterium that causes bacterial pustule disease in soybean. To acclimate to new environments, the expression of genes in bacteria is controlled directly or indirectly by diverse transcriptional factors. Among them, LysR type transcriptional regulators are well-characterized and abundant in bacteria. In a previous study, comparative proteomic analysis revealed that LysR type carbohydrate-related transcriptional regulator in Xag (LcrX) was more abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 87 publications
1
17
0
Order By: Relevance
“…The first transcriptional factor described that specifically responds to HOCl, YjiE, belongs to the family LysR-type transcriptional regulator (LTTR) [ 111 ]. LTTR, the largest family of transcriptional regulators described in prokaryotes, is composed of a helix-turn-helix (HTH) on its DNA binding domain (DBD) and a regulatory domain (RD) that can activate or repress gene expression [ 112 ]. It regulates the transcription of several genes, including those involved in adherence [ 113 ], efflux pump [ 114 ], antibiotic resistance [ 115 ], biofilm formation [ 116 ], and oxidative stress response [ 117 ].…”
Section: Adaptive Response Of Gram-negative Cells To Hoclmentioning
confidence: 99%
“…The first transcriptional factor described that specifically responds to HOCl, YjiE, belongs to the family LysR-type transcriptional regulator (LTTR) [ 111 ]. LTTR, the largest family of transcriptional regulators described in prokaryotes, is composed of a helix-turn-helix (HTH) on its DNA binding domain (DBD) and a regulatory domain (RD) that can activate or repress gene expression [ 112 ]. It regulates the transcription of several genes, including those involved in adherence [ 113 ], efflux pump [ 114 ], antibiotic resistance [ 115 ], biofilm formation [ 116 ], and oxidative stress response [ 117 ].…”
Section: Adaptive Response Of Gram-negative Cells To Hoclmentioning
confidence: 99%
“…Xag can be spread by rain droplets during the growing season and by seed transportation 7 . A number of spreads of bacterial pustule disease have taken place in Asia during recent years, reducing the size and quantity of the seeds 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…7 A number of spreads of bacterial pustule disease have taken place in Asia during recent years, reducing the size and quantity of the seeds. 8,9 Flavonoids rutin and genistein have been directly related to the defence mechanism of soybean to Xag, and soybean resistant varieties are known to produce higher amounts of flavonoids in comparison with susceptible varieties. 10,11 Although soybean has been reported to produce Biochanin A, the concentration of this isoflavonoid is under the quantification limits, indicating that soybean can synthesize Biochanin A only in very low concentration.…”
Section: Introductionmentioning
confidence: 99%
“…However, among the final 22 immunogenic proteins, only MbovP274 was unique to P1. Although it is highly immunogenic, the conserve domain database (CDD) prediction showed that this protein contains a highly conserved LysR transcriptional regulatory protein family domain that is involved in virulence and biofilm formation [ 24 ]. MbovP296 and MbovP518 are unique to P150.…”
Section: Discussionmentioning
confidence: 99%